The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6cc00291a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and properties of a benzofuran-based cage-shaped borate: photo activation of Lewis acid catalysts

Abstract: A cage-shaped borate with benzofuran moieties was synthesized. This borate showed a higher degree of catalytic activity for Mukaiyama-aldol type reactions than a simple benzene-based cage-shaped borate induced by self-aggregation. Moreover, the exposure of the complex to black-light irradiation enhanced the catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The effect of alkyl groups on the shift of the Δν(C=O) value was minimal; borate 1 k B, with three butyl groups, exhibited the same value as that of 1 a B. According to our previous studies, [52, 55, 57] we calculated the LUMO energy levels of the cage‐shaped borates. The calculated LUMO levels at the B3PW91/6‐31+G**//B3PW91/6‐31G** level correlated with the experimental observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of alkyl groups on the shift of the Δν(C=O) value was minimal; borate 1 k B, with three butyl groups, exhibited the same value as that of 1 a B. According to our previous studies, [52, 55, 57] we calculated the LUMO energy levels of the cage‐shaped borates. The calculated LUMO levels at the B3PW91/6‐31+G**//B3PW91/6‐31G** level correlated with the experimental observations.…”
Section: Resultsmentioning
confidence: 99%
“…The high accessibility of the tripodall igand has ensured that chemicalm odifications of cage-shaped Lewis acids, which lead to fine control of the Lewis acidity, [55,56] enablesavariety of catalytic activities. [57][58][59] The feasibility of chemical modifications of complex 1bBp rompted us to investigate the electronic and/or geometrice ffects of a p-pocketo nm olecular recognition. To assess these factors, we designedt hree types of cage-shaped borates by changingt he ortho substituents.…”
Section: Introductionmentioning
confidence: 99%
“…In Lewis acid catalysis, the effective activation of substrates by Lewis acidity and the smooth release of products from a catalyst are essential for achieving a high turnover frequency, and so tuning of the Lewis acidity is necessary in efficient catalysis design. The Lewis acidities of 1 ‐AlX 2 and 2 ‐AlX 2 were estimated from the Δ ν (C=O) value of pyrone 4 in the complexation between aluminum compound Al and 4 (Table ) . The observed values suggested that chloro complexes 1 ‐AlCl 2 and 2 ‐AlCl 2 have low and moderate Lewis acidities, respectively (entries 1 and 2), and the perchlorate and triflate complexes (entries 3–5) have high Lewis acidities comparable to those of AlCl 3 , Al(ClO 4 ) 3 , and Al(OTf) 3 (entries 6–8) .…”
Section: Figurementioning
confidence: 99%
“…X -ray diffraction measurements of Lewis acid-base adduct 1-AlCl 2 ·3 ( Figure 4A In Lewis acid catalysis, the effective activation of substrates by Lewis aciditya nd the smooth release of products from a catalysta re essential fora chieving ah igh turnover frequency, and so tuning of the Lewis acidity is necessary in efficient catalysis design.The Lewis acidities of 1-AlX 2 and 2-AlX 2 were estimated from the Dn(C=O) value of pyrone 4 in the complexation between aluminum compound Al and 4 ( Table 1). [13] The observed values suggested that chloro complexes 1-AlCl 2 and 2-AlCl 2 have low and moderate Lewis acidities, respectively (entries 1a nd 2), and the perchlorate and triflate complexes (entries 3-5) have high Lewis acidities comparablet ot hose of AlCl 3 ,A l(ClO 4 ) 3 ,a nd Al(OTf) 3 (entries 6-8). [14] Pentacoordinate 2-AlCl 2 showed al ower Lewis acidity comparedt ot he moderate Lewis acidityo ft etracoordinate 1-AlCl 2 (entries 1a nd 2), which is consistent with al ack of complexation between 2-AlCl 2 and 3.I nc ontrast, 2-Al(ClO 4 ) 2 showed ah igher Lewis acidity than 1-Al(ClO 4 ) 2 (entries 3a nd 4), which may be due to the dissociation of aC lO 4 ligand from the 2-Al(ClO 4 ) 2 ·4 complex to generate ac ationic complex in the solution state.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] We recently established the effectivenesso facage-shapedt riphenolic ligand in controlling the Lewisa cidity of ab oron atom. [10][11][12] As shown in Figure 1a,t he Lewis acidity of the cage-shaped borate 1Bc an be precisely tuned by changingt he tethered atom (X), [13] the p-conjugated system (p) [14] and/or the substituents (R). [15] The introduction of substituents (R), such as halogens [15] and aryl groups, [11] and p-conjugated systems( p) [14] can be used to electronically tune the Lewis acidity of ac age-shaped borate, which can also be sterically controlled by changing the tethered atom, X, from carbon to silicon, [13] whicha llows precise controlo ft he LUMO levels and dihedral angleso fC (Ar ipso )-O-B-O in the cage.…”
mentioning
confidence: 99%